Experiencing European integration : transnational lives and European identity / Theresa Kuhn. - Kuhn, Theresa (Oxford University Press, 2015)
European integration has generated a wide array of economic, political, and social opportunities beyond the nation state. An early theorist of European integration, Karl Deutsch, expected this development to promote a collective identity and public support for European integration: by interacting across borders, Europeans would eventually acquire a common 'we feeling'. This book puts these expectations under scrutiny by developing a comprehensive theoretical model that helps us understand how transnational interactions relate to orientations towards European integration.